PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN (STUDI PADA CV. PUTRA PUTRI JOMBANG) - Septian Ragil Anandita; Mohammad Baharudin; Wisnu Mahendri (Sekolah Tinggi Pariwisata Mataram, 2021)
This research was conducted at CV. Putra Putri of Jombang. The purpose of this study was to examine and analyze the effect of work motivation and career development on employee performance at CV. Putra Putri of Jombang. This type of research is quantitative research with survey method. In collecting data using non-probability sampling technique. The population of this study were all employees of CV. Putra Putri Jombang, so that the sample in this study was 50 respondents. To analyze the data obtained using the Classical Assumption Test, Multiple Linear Regression and correlation coefficient using the F Test (Simultaneous Test), T Test (Partial Test). Meanwhile, data collection was carried out through several techniques, including field studies and questionnaires. The results of research and data processing indicate that the two independent variables, namely work motivation and career development simultaneously have a significant effect on employee performance. The results of the correlation coefficient test show that the R value of 0.963 means that work motivation and career development together have a strong relationship to employee performance, while the results of the coefficient of determination test show that the R² value is 0.927, then the R² value < 1 means 92.7% the influence of motivation work and career development have a significant effect on employee performance at CV. Son and Daughter of Jombang. While the rest (92.4%) is influenced by other variables outside the study. It is expected that the things that must be considered to further improve the performance of employees at CV. Putra Putri Jombang, namely conducting training, internships, entrepreneurship seminars, job rotations and so on.